2018
DOI: 10.1186/s13017-018-0178-1
|View full text |Cite
|
Sign up to set email alerts
|

Differentiation in an inclusive trauma system: allocation of lower extremity fractures

Abstract: BackgroundImplementation of an inclusive trauma system leads to reduced mortality rates, specifically in polytrauma patients. Field triage is essential in this mortality reduction. Triage systems are developed to identify patients with life-threatening injuries, and trauma mechanisms are important for triaging. Although complex extremity fractures are mostly non-lethal, these injuries are frequently the result of a high-energy trauma mechanism. The aim of this study is to compare injury and patient characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Regarding the differences in the LOS, a multicenter analysis from the Netherlands demonstrated longer hospitalisation at HVCs for fractures of the lower extremities. This was attributed in particular to the severity of the trauma (which is probably also the cause in our study) and the accompanying injuries [ 32 ]. Jain et al showed a decreased LOS with higher surgeon case load for humerus fractures [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the differences in the LOS, a multicenter analysis from the Netherlands demonstrated longer hospitalisation at HVCs for fractures of the lower extremities. This was attributed in particular to the severity of the trauma (which is probably also the cause in our study) and the accompanying injuries [ 32 ]. Jain et al showed a decreased LOS with higher surgeon case load for humerus fractures [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 1999 the Netherlands implemented an inclusive trauma system, which organized the country in 11 trauma regions [9]. The goal of this inclusive system is to present all patients on a timely basis at the right hospital, with the centralisation of the most severely injured patients in level 1 centres [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The less severely injured patients are ideally treated at level 2 and level 3 centres.…”
Section: The Evolution Of Mortality In Traumamentioning
confidence: 99%
“…This organizational change had a major impact on trauma care, as it did in most countries that implemented inclusive trauma systems [24,25]. The data presented in every time period is based on previous publications and where possible adjusted odd ratios presented in those publications were used [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Before centralisation (step 1) a regional mortality rate of 2.6% was documented, of which 40% died due to exsanguination.…”
Section: The Evolution Of Mortality In Traumamentioning
confidence: 99%
“…Dass ein multidisziplinärer Ansatz bei komplexen Verletzungen häufig nur in einem überregionalen Zentrum gelingen kann, konnten Würdemann et al. zeigen [ 27 ]. Diese Behandlungsansätze haben bisher aber noch keine feste Implementierung in der Klinik.…”
Section: Von Der Tumorkonferenz Bis Zur Interdisziplinären Muskuloskeunclassified